Effect of Dietary Methylsulfonylmethane Supplementation on Growth Performance, Hair Quality, Fecal Microbiota, and Metabolome in Ragdoll Kittens - Guo, Dan; Zhang, Limeng; Zhang, Lingna; Han, Sufang; Yang, Kang; Lin, Xinye; Wen, Chaoyu; Tong, Aorigeile; Zhang, Meiyu; Yin, Yulong; Deng, Baichuan (Frontiers in Microbiology, 2022)
Methylsulfonylmethane (MSM) is a natural sulfur-containing organic substance which has many biological functions, such as antioxidant and anti-inflammatory, skin nourishing, and promoting hair growth. This study was conducted to determine the effect of MSM supplementation on the growth performance, antioxidant capacity, and hair quality in kittens. A total of 21 Ragdoll kittens (6 to 8-months-old; male: female = 7:14) were included and randomly assigned to three groups. The three groups of kittens were fed three diets, the control (CON; no MSM), low dose (LMSM; 0.2% MSM in diet) and high dose (HMSM; 0.4% MSM in diet), respectively for 65 days. During the whole period, the food intake (FI) of kittens in the CON group decreased (P = 0.069) compared with that of kittens in the MSM groups, and the average daily gain (ADG) of kittens in MSM groups were numerically higher than that in CON. The scale thickness of the hair of kittens tended to be lower in LMSM group compared with that in CON group (P = 0.073). And the scale thickness of hair from kittens in LMSM differed (P = 0.023) between d 0 and d 65, indicating that the hair softness and glossiness of kittens in LMSM group improved over time. Also, kittens fed MSM had a lower abundance of fecal Actinobacteriota, Subdoligranulum, Libanicoccus and Lachnospiraceae-NK4A136-group and higher Collinsella, Methylobacterium-Methylorubrum, Sphingomonas and Herbaspirillum. No significant differences in short-chain fatty acids (SCFAs) were observed among treatment groups. Fecal metabolomics analysis also revealed that MSM markedly affected the metabolism of lipid, cofactors,vitamins, and amino acid. Together, these results showed that dietary supplementation with MSM, especially LMSM, can enhance the growth performance and hair quality of kittens. Besides, the fact that supplementation with MSM did not cause detrimental effects on serum chemistry supports the safety inclusion of MSM at the current dosage in feline diets.